Analisis Strategi Pemasaran Digital pada Platform Fintech Syariah untuk Meningkatkan Daya Saing di Keuangan Islam - Tia Nurazizah; Dea Safitri; Dini Selasi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the digital marketing strategies implemented by Islamic fintech platforms to enhance their competitiveness in the Islamic financial sector. The research is motivated by the rapid development of financial technology, which has significantly influenced consumer behavior and reshaped financial institutions’ business models, including those operating under Islamic principles. Despite this growth, Islamic fintech faces challenges in strengthening its brand image, user trust, and customer loyalty amidst the dominance of conventional fintech players. The study adopts a qualitative descriptive approach using case studies of selected Islamic fintech platforms such as Ammana, Ethis, and Investree Syariah. Data were collected through documentation, online interviews, and analysis of financial reports and official websites. The data were analyzed using the SWOT framework to identify the strengths, weaknesses, opportunities, and threats of current digital marketing strategies. The findings indicate that the use of social media, collaboration with Muslim influencers, and educational content about halal finance serve as key strategies for expanding market reach and building user trust. Consistent and Sharia-compliant digital marketing efforts have proven effective in enhancing brand awareness, customer loyalty, and Islamic financial inclusion. The implications of this research suggest that digital marketing is not merely a promotional tool but a strategic instrument to strengthen competitiveness and expand the global presence of Islamic fintech. With supportive regulations and improved digital literacy, Islamic fintech has the potential to become a driving force in transforming the Islamic financial ecosystem in the digital era.